Case Report, Practices Survey and Literature Review of an Under-Recognized Pediatric Vascular Disorder: The BASCULE Syndrome - Baurens, Natacha; Briand, Clémence; Giovannini-Chami, Lisa; De Guillebon De Resnes, Jean-Marie; Hubiche, Thomas; Chiaverini, Christine; Giordana, Pascal; Leftheriotis, Georges; Bernardor, Julie (Frontiers in Pediatrics, 2022)
Introduction: Bier anemic spots, cyanosis, and urticaria-like eruption (BASCULE) syndrome is an under-reported pediatric vascular disorder from the group of acrosyndromes. In children, these include paroxysmal acrosyndromes (Raynaud's phenomenon, chilblain-like lesions), permanent acrosyndromes (acrocyanosis), and transient acrosyndromes, the pathogenesis of which is associated with virus infections, Epstein-Barr virus and more recently SARS-CoV-2. Methods: We report a case of BASCULE syndrome associated with a Postural Orthostatic Tachycardia Syndrome (POTS) and provide a narrative review of case reports describing BASCULE syndrome in children. Moreover, we present the results of a prospective practices survey we performed in the French medical community. Results: A 14-years-old boy reported pruritic erythrocyanic lesions on the lower limbs which occurred in standing position and fully resolved when he lied down. He reported asthenia and cramps. He presented a typical BASCULE syndrome associated with POTS confirmed by tilt-test. Physical and vascular examinations were within normal range. We identified 12 case reports, describing 21 pediatric cases since 2016. Most patients were adolescents between 12 and 19 years of age or newborns. 20% of cases in the literature have presented POTS or orthostatic intolerance. Our survey among 95 French physicians confirmed that BASCULE syndrome is an under-diagnosed and under-recognized disease in the general pediatric practice, at least in France. 65% had already encountered patients with similar symptoms, but only 30% declared that they had knowledge of the BASCULE syndrome. Conclusion: The under-recognition of the clinical manifestations leads the patients to consult emergency, with multiple unnecessary investigations performed. We suggest that diagnosis of BASCULE syndrome remains based on clinical observations, with no need for laboratory tests to avoid unnecessary health costs. We enhance physicians to perform a tilt test when POTS is suspected.